2021
DOI: 10.1007/s10758-021-09546-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of digital competence of educators (DigCompEdu) in teacher trainees: the context of Melilla, Spain

Abstract: The Spanish autonomous city of Melilla, located in northwest Africa, has one of the highest academic failure and abandonment rates in Europe. An effective way to improve this situation would be to improve students’ digital competence. In order to do so, teachers must have competent digital skills themselves and also be able to teach them. To determine teachers’ level of digital competence, the Spanish adaptation of the European Framework for Digital Competence of Educators was used to analyse the self-assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 72 publications
2
25
0
2
Order By: Relevance
“…On the whole, many of our participants’ beliefs coincide with the findings of previous research that showed a dearth of knowledge pertaining to data privacy in general populations (Obar & Oeldorf-Hirsch, 2018 ; Sander, 2020 ), and among PSTs (García-Vandewalle et al, 2021 ; Milton et al, 2021 ). Our findings align with research that has highlighted an absence of teacher preparation for issues related to personal data awareness and practices (Gallego-Arrufat et al, 2019 ), especially related to commercial privacy (Vartiainen et al, 2022 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the whole, many of our participants’ beliefs coincide with the findings of previous research that showed a dearth of knowledge pertaining to data privacy in general populations (Obar & Oeldorf-Hirsch, 2018 ; Sander, 2020 ), and among PSTs (García-Vandewalle et al, 2021 ; Milton et al, 2021 ). Our findings align with research that has highlighted an absence of teacher preparation for issues related to personal data awareness and practices (Gallego-Arrufat et al, 2019 ), especially related to commercial privacy (Vartiainen et al, 2022 ).…”
Section: Resultssupporting
confidence: 88%
“…Gallego-Arrufat et al ( 2019 ) identified that nearly half of Spanish and Portuguese PSTs who participated in a survey ( N = 317) demonstrated insufficient awareness of fundamental concepts related to personal data privacy such as digital identity, footprint, and online reputation. A study with 176 Spanish PSTs based on the DigCompEdu framework showed that although PSTs had relatively high levels of digital competence, those levels did not progress over time, which could mean that digital competence was not addressed during their teacher education (García-Vandewalle et al, 2021 ). In particular, the authors concluded that the main limitation in the Spanish PSTs’ digital competence is their lack of skills for digital security (competence area “Safety” in the DigComp framework).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After studying the level of digital competence demonstrated by the teachers in the Spanish city of Melilla, García-Vandewalle García et al [20], point to the gaps in the digital competence of both the groups, students and teachers, especially in terms of security. Next, they provide their recommendations as to overcoming the difficulties to bridge these gaps.…”
Section: New Trends and Strategies In The Modern Educational Processmentioning
confidence: 99%
“…García-Vandewalle García et al emphasize that the collective search for information in databases, i.e. the ability to cooperate, also influences the increase in the level of digital competence of students [20]. Yet, there is no holistic approach in [20] to the study of factors, which affect the level of digital competence of students.…”
Section: New Trends and Strategies In The Modern Educational Processmentioning
confidence: 99%
“…engagement García-Vandewalle García et al (2021). develop the Common Framework for the Digital Competence of Teachers, which is adapted from the DigCompEdu, to assess the self-perception of the digital competence of Spanish teachers by using a four-point Likert scale questionnaire.Rizal et al (2021) combine a 5-point Likert scale questionnaire and a guided interview to test the digital literacy of teachers.…”
mentioning
confidence: 99%